Synthesis and characterization of Silver nanoparticles: A review - Ekhlas A. Abdul Kareem; Alaa E. Sultan; Hadeel M. Oraibi (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2023)
In the current century, nanotechnology has gained great interest due to its ability to modify the size of metals to the nanoscale, which dramatically changes the physical, chemical, and biological characteristics of metals relative to their bulk counterparts. The approaches used to create nanoparticles (NPs) are physical, و chemical and وbiological. The shortcomings in physical and chemical synthesis approaches, such as the generation of toxic by-products, and energy consume as they require high temperature, pressure, power and lethal chemicals, contributed to an increased interest in biological synthesis by plants. Scientists have created a new filed called as "green nanotechnology" by fusing the idea of sustainability with nanotechnology. By substituting plant-based materials, it aims to reduce the amount of chemicals used in the manufacture of nanoparticles. Silver nanoparticles (AgNPs) attract the most attention due to their great stability and low chemical reactivity in comparison to other metals. The present review describes the fabrication of nanoparticles (NPs) via chemical and physical methods, as well as the use of plants, bacteria, and fungi. The current review also discusses certain analytical methods used to examine AgNPs, including UV-Vis spectroscopy, FT-IR, SEM, TEM, AFM, XRD, DLS, and zeta potential analysis